Implementation of social and semantic tools into open educational resources production - Rodriguez Morales, G. (2011)
The present paper shows the Word made to implement of one production cycle of OERs using Social and Semantic Resources into an OCW repository of a high level educational institution which has allowed to prove the proposal of OER s production cycle based on ADDIE instruction design model. © 2011 IEEE.